Revision of Bilateral Celft Lip Deformity Using Abbe Flap - Djaprie, Shelly M; Kreshanti, Prasetyanugraheni; Handayani, Siti; Bangun, Kristaninta (Lingkar Studi Bedah Plastik Foundation, 2013)
Background: Most primary repair of bilateral complete cleft lip does not show satisfying result due to several deformities caused by inappropriate use of the hypoplastic prolabial tissue, failure to advance the lateral lip elements to the midline for primary repair of the orbicularis, and scarring. The Abbe flap is the accepted procedure for the correction of severe secondary deformity of a bilateral cleft lip. By introducing an adequate amount of lip tissue, it relieves the tightness of the upper lip and also corrects the depressions of the tip of the nose. Symmetry between the two lip is also achieved Patient and Method: Three patients with tight lip deformity underwent this procedure. The Abbe flap, which was taken from the central portion of the lower lip vermilion, was designed to repair the vermilion tubercle and the Cupid’s bow. A tiny portion of skin was included to facilitate closure of the donor site. The pedicle was divided 3 weeks after operation. Results: Each patients showed a more natural contour of the vermilion tubercle and the Cupid’s bow. The scarring of the donor site was inconspicuous. Summary: The Abbe flap can be considered as a choice for revision of bilateral cleft lip deformity. The disadvantages of this flap include patient’s discomfort and the need for multiple procedures.